SolidWorks : sheet metal - Keraste, Dean (InfiniteSkills, 2013)
"In this video based SolidWorks - Sheet Metal training course, expert trainer Dean Kerste will show you how to successfully navigate through the SolidWorks sheet metal environment. The SolidWorks sheet metal functionality allows you to create sheet metal part designs quickly and effectively, accelerating the design process and increasing your productivity. This course is designed for the user that already has a fundamental understanding of SolidWorks. You will start out by learning how to create sheet metal parts. Dean will take you through this process step by step, covering everything from creating a base flange to a closed corner. You will move into learning about the sheet metal forming tools, and how to modify existing tools and create new ones. From there, Dean will show you how to convert to sheet metal, use the rip feature, and add a welded corner. This training course will also show you additional sheet metal features such as lofted bends and how to create cross breaks. Finally, you will go through a certification preparation and be able to test your developed skills with a practice exam. Once you have completed this computer based training course, you will have an in-depth understanding of how to create sheet metal parts in SolidWorks. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.